High-Density Lipoprotein Subfractions and Cholesterol Efflux Capacity Are Not Affected by Supervised Exercise but Are Associated with Baseline Interleukin-6 in Patients with Peripheral Artery Disease - Albaghdadi, Mazen S.; Wang, Zheng; Gao, Ying; Mutharasan, R. Kannan; Wilkins, John (Frontiers in Cardiovascular Medicine, 2017)
Objective To quantify the association between high-density lipoprotein (HDL) subfractions, efflux capacity, and inflammatory markers at baseline, and the effect of supervised exercise on these HDL parameters in patients with peripheral artery disease (PAD). Methods The Study to Improve Leg Circulation (SILC) was a randomized trial of supervised treadmill exercise, leg resistance training, or control in individuals with PAD. In a post-hoc cross-sectional analysis, we quantified the associations between baseline HDL subfraction concentrations (HDL2 and HDL3), HDL cholesterol efflux capacity, and inflammatory markers (C-reactive protein [CRP] and interleukin-6 [IL-6]). We then examined the effect of supervised exercise on changes in these lipoprotein parameters and inflammatory markers in 88 patients from SILC. Results Baseline HDL cholesterol efflux capacity was associated with baseline concentrations of HDL2 (β=0.008, P=0.0106), HDL3 (β=0.013, P<0.0001), and IL-6 (β=-0.019, P=0.03). Baseline HDL3 concentration was inversely associated with IL-6 concentration (β =-0.99, p=0.008). Compared to control, changes in HDL2, HDL3, normalized HDL cholesterol efflux capacity, CRP, or IL-6 were not significantly different at 6-months following the structured exercise intervention. Conclusion HDL efflux and HDL3 were inversely associated with IL-6 in PAD patients. Structured exercise was not associated with changes in HDL subfractions, HDL cholesterol efflux capacity, CRP, and IL-6 in PAD patients. Our preliminary findings support the theory that inflammation may adversely affect HDL structure and function, however further studies are needed evaluate these findings.